Histopathological gill changes in wild leaping grey mullet (Liza saliens) from the Esmoriz-Paramos coastal lagoon, Portugal - Fernandes, Conceição (2011)
The histopathological changes are among the most recognized responses to environmental stressors, namely heavy metals. Liza saliens were sampled, in the Portuguese Esmoriz-Paramos coastal lagoon to assess their gill histopathological response to Cu and Zn contaminated sediments. A lesion prevalence index, severity, and extension scores of each lesion, as well as an assessment value (severity extension), were determined to evaluate the effect of environmental heavy metal exposure. The main histopathological changes observed were aneurisms, hyperplasia, lifting, and vasodilation. A high prevalence for each lesion (65–85%) was found, in addition to a high number of simultaneous lesions. Vasodilation and hyperplasia were the lesions that showed higher prevalence indexes. Lifting, followed by hyperplasia, were the lesions with highest assessment value. The prevalence of the number of the lesions found in L. saliens collected from the Esmoriz-Paramos lagoon was high when compared with mullet caught in the sea. A previous work revealed that fish collected in the lagoon showed elevated Cu and Zn levels in their gills, in a positive correlation with age. However, no positive correlation was observed between assessment value and gill metal levels.